2013
DOI: 10.1177/1534765613477500
|View full text |Cite
|
Sign up to set email alerts
|

Themes of resilience and growth in survivors of politically motivated violence.

Abstract: The experiences of 19 Israeli civilian survivors of politically motivated violence (PMV) between 2001 and 2003 were examined using in-depth interviews to elicit resonating narratives. The narratives were informed by demographic data and the Posttraumatic Growth Inventory (PTGI) and Posttraumatic Stress Disorder Symptom Scale (PSS) self-report surveys. Four meaningful groupings or patterns of change emerged, reflecting various ways to experience the trauma of PMV: little or no growth, living the attack, resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…The identification of personal strength is another domain of posttraumatic growth that has had a positive effect on resilience and psychological benefits (Konvisser, 2013;Tedeschi & Calhoun, 2004). In a study of women coping with abusive relationships, Cobb, Tedeschi, Calhoun, and Cann (2006) found that the majority of participants realized that they had inner strength and the ability to overcome negative circumstances and, as such, tended to value the current life situation.…”
Section: Posttraumatic Growth Domainsmentioning
confidence: 99%
“…The identification of personal strength is another domain of posttraumatic growth that has had a positive effect on resilience and psychological benefits (Konvisser, 2013;Tedeschi & Calhoun, 2004). In a study of women coping with abusive relationships, Cobb, Tedeschi, Calhoun, and Cann (2006) found that the majority of participants realized that they had inner strength and the ability to overcome negative circumstances and, as such, tended to value the current life situation.…”
Section: Posttraumatic Growth Domainsmentioning
confidence: 99%
“…Esta suerte de catarsis colectiva ayudaría al auto-reconocimiento de las propias fortalezas, facilitando un sentido de competencia personal y colectiva, que, de alguna manera, se refleja en sus imágenes personales (Tamayo, 2003;Crisóstomo, 2014), más aún cuando la identificación organizacional pasa también por el plano familiar. Resultados también similares a la evidencia sobre CPT y al rol del soporte social en tanto entornos que legitiman lo vivido y motivan su expresión (Tedeschi y Calhound, 2004;Prati y Pietrantoni, 2009;Konvisser, 2013). Enfatizar también los espacios para el duelo y la vinculación simbólico con sus desaparecidos que brinda ANFASEP (Peña, 2017).…”
Section: Resultsunclassified
“…Entre las bases que facilitan el CPT, se identifican básicamente dos: (a) el procesamiento cognitivo y afectivo del evento y (b) el soporte brindado por un entorno significativo. El primero, refiere al ejercicio centrado en darle sentido a lo vivido y explicitar consecuencias y opciones (Konvisser, 2013;Chan et al 2016). El segundo, lo relacional, alude a asociaciones significativas entre el soporte social y el CPT a raíz de contar con un entorno que acompañe y sostenga (Volgin y Bates, 2016) y facilite el afrontamiento y adaptación a la crisis y la creación de narrativas sobre lo vivido (Prati y Pietrantoni, 2009;Konvisser, 2013).…”
Section: El Crecimiento Postraumático Como Articulador Entre La Conecunclassified
“…This study utilizes policy process research techniques and follows the methodology in Konvisser's (2012Konvisser's ( , 2013Konvisser's ( , 2015 previous exploration of the psychological consequences of wrongful conviction (see also Clifford, n.d.). Data collection begins with pre-questionnaires to collect background information about the individuals and their wrongful conviction experiences, and their participation in innocence policy work.…”
Section: Methodsmentioning
confidence: 99%
“…The research goals of this study draw on theories of resilience and posttraumatic growth that focus on the possibility of positive psychological outcomes and wellness alongside continuing distress as a result of the struggle with a highly challenging life circumstance (Frankl, 2006;Tedeschi & Calhoun, 2004) and seek to understand how one might move beyond the trauma of such events (see Konvisser, 2012Konvisser, , 2013Konvisser, , 2014Konvisser, , 2015Konvisser, , 2016.…”
Section: Theoretical Frame Research Goals and Broader Impactsmentioning
confidence: 99%